POLITIK DINASTI DITENGAH SISTEM DEMOKRASI: MENYIMAK ISU REPUBLIK RASA KERAJAAN - Jiddan Gamal Qondas; Sutopo (The Republic : Journal of Constitutional Law, 2024)
Dynastic politics is actually just a term in political science which means the process of directing the regeneration of power for the interests of certain groups with the aim of gaining or maintaining power in a country. In democratic countries, this term often appears, even though in democratic countries, power is in the hands of the people, which is where the term dynastic politics first appeared. is when royal power or absolute monarchy, where power is passed on/inherited from the previous ruler to the next ruler. Indonesia is a country that has a democratic system, namely sovereignty is in the hands of the people, this is in accordance with the preamble to the 1945 Constitution, a fragment of the fourth paragraph which states "then the independence of the Indonesian nation was formulated in a Constitution of the State of Indonesia, which was formed in the structure of the Republic of Indonesia. Indonesia has the sovereignty of the people, but in reality there are a handful of people who have influence and power in a region, giving rise to the ambition that with power, business and family interests can be secured, because the high price of political dowry when wanting to become a public official in Indonesia results in only people It is true that certain people can become officials, it is true that it is the people who determine the winning vote in a democratic country, but it should be noted that Money Politics still applies, from the ruler who is elected and has good prestige, this results in the ruler holding a great legacy so that family and close people can also enjoy it. as a Privilege.